The Effect of Transformational Leadership on Job Satisfaction: A Systematic Literature Review - M. Zaki Yerilwan Putra (CV. Syntax Corporation Indonesia, 2024)
The business environment is increasingly complicated and competitive so business people must be more responsive. In order to remain relevant, the role of leaders must be maximized in developing and advancing the human resources they have. This is still a problem with the leadership style applied in a business organization. The transformational leadership style is a solution to companies' anxiety in facing an increasingly dynamic and disruptive business environment. This research aims to find out how transformational leadership style can impact job satisfaction. The research method used in this research is a systematic literature review taken from 2018-2023. Transformational leadership is applied more often because it has a high level of satisfaction and has a significant influence on commitment and work performance. Transformational Leadership Style has a positive relationship with job satisfaction.